2022
DOI: 10.1371/journal.ppat.1010464
|View full text |Cite
|
Sign up to set email alerts
|

Inducible CRISPR activation screen for interferon-stimulated genes identifies OAS1 as a SARS-CoV-2 restriction factor

Abstract: Interferons establish an antiviral state through the induction of hundreds of interferon-stimulated genes (ISGs). The mechanisms and viral specificities for most ISGs remain incompletely understood. To enable high-throughput interrogation of ISG antiviral functions in pooled genetic screens while mitigating potentially confounding effects of endogenous interferon and antiproliferative/proapoptotic ISG activities, we adapted a CRISPR-activation (CRISPRa) system for inducible ISG expression in isogenic cell line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 115 publications
(170 reference statements)
1
27
0
Order By: Relevance
“…Most antiviral resistance factors are Interferon Stimulated Genes (ISGs), in other words, genes that activate their expression after detecting interferons by cellular receptors (Schneider et al, 2014;Danziger et al, 2022). Binding interferon to their receptors triggers a series of signaling cascade in the cell to protect against an infection.…”
Section: Resistance Susceptibility and Permissibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most antiviral resistance factors are Interferon Stimulated Genes (ISGs), in other words, genes that activate their expression after detecting interferons by cellular receptors (Schneider et al, 2014;Danziger et al, 2022). Binding interferon to their receptors triggers a series of signaling cascade in the cell to protect against an infection.…”
Section: Resistance Susceptibility and Permissibilitymentioning
confidence: 99%
“…Binding interferon to their receptors triggers a series of signaling cascade in the cell to protect against an infection. ISGs encode functionally diverse gene products, including the antiviral effectors that antagonise distinct steps of viral life cycles (Schoggins, 2019;Danziger et al, 2022). As they depend on an interferon stimulus, induced resistance usually is not a concern for in vitro virology studies, as most cell lines used for viral production do not produce endogenous interferons.…”
Section: Resistance Susceptibility and Permissibilitymentioning
confidence: 99%
“…There are three OAS family proteins (OAS1, OAS2, OAS3) present in humans. A recent report using a CRISPR activation screen identified OAS1 as a major antiviral factor in restricting SARS-CoV-2 infection [ 23 ]. Notably, in this CRISPRa screening study [ 23 ], OAS2 and OAS3 were not identified to have an antiviral role.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report using a CRISPR activation screen identified OAS1 as a major antiviral factor in restricting SARS-CoV-2 infection [ 23 ]. Notably, in this CRISPRa screening study [ 23 ], OAS2 and OAS3 were not identified to have an antiviral role. However, in our study, we found that all three OAS genes—OAS1, OAS2 and OAS3—were induced in severe COVID-19 samples and may have implications on host response to COVID-19 ( Figure 1 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme synthesizes oligomers that activate RNAse L, which degrades cellular and viral RNA and impairs viral replication [ 70 ]. Danziger et al found that OAS1 catalytic activity is required for antiviral response against SARS-CoV-2 [ 71 ]. Moreover, a membrane-associated OAS1 form could act as a ds-RNA sensor in infection sites.…”
Section: Discussionmentioning
confidence: 99%